Management of Home Visits in the Implementation of Counseling Support Activities in High Schools in Indonesia - Salsabila Nasution; Firman; Neviyarni; Bin Che Amat, Muhammad Asyraf (Risalah, Jurnal Pendidikan dan Studi Islam, 2023)
High school students cannot be separated from problems and problems due to the demands of an increasingly complex era. Counseling guidance is present in helping students to overcome individual problems. The implementation of services from counseling guidance requires a management function so that the implementation of services becomes systematic. One of the supporting activity services in counseling guidance that needs a management function is home visits, home visits involve several parties in their implementation so that planning and organization is needed before implementation so that there are no problems with related parties. The research method in this study was descriptive qualitative with the research location being SMA Negeri 10 Medan. Data collection was carried out by participant observation, interviews and document analysis. The results of this study revealed that the counseling teacher had carried out home visits but specifically there were several aspects that the counseling teacher had to pay attention to in carrying out home visits for students.